PERBEDAAN ANTARA GABAPENTIN AMITRIPTILIN DAN KOMBINASI GABAPENTIN DENGAN AMITRIPTILIN DALAM MENGURANGI INTENSITAS NYERI PADA NYERI NEUROPATI DIABETIKA - Franz Julius Hutapea, Aida Fithrie, Kiki Muhammad Iqbal, Yuneldi Anwar (NEURONA, 2013)
INTRODUCTION PAIN IS THE MOST DISTURBING SYMPTOM OF DIABETIC NEUROPATHY PAINFUL DIABETIC NEUROPATHY OCCURS IN 1626 OF PATIENTS WITH DIABETES MELLITUS VARIETIES OF MEDICATIONS ARE STILL BEING STUDIED TO GET THE BEST TREATMENT FOR PAINFUL DIABETIC NEUROPATHY